Construction and Validation of a Brief Pandemic Fatigue Scale in the Context of the Coronavirus-19 Public Health Crisis - Esther Cuadrado; Esther Cuadrado; Miguel A. Maldonado; Miguel A. Maldonado; Carmen Tabernero; Carmen Tabernero; Carmen Tabernero; Alicia Arenas; Alicia Arenas; Rosario Castillo-Mayén; Rosario Castillo-Mayén; Bárbara Luque; et al. (Frontiers Media S.A., 2021)
Objectives: The chronic restrictions to mitigate the new SARS-CoV-2 virus may result in pandemic fatigue. This study set out to develop a short, reliable, valid, and gender-invariant instrument-the Pandemic Fatigue Scale (PFS).Methods: In the first phase, 300 students responded to a pilot questionnaire that allowed the reduction and refinement of the items. In the second phase, the validity, reliability, and invariance of the scale were explored among a sample of 596 participants.Results: Factor exploratory and confirmatory analyses confirmed a robust adjustment for the bifactorial structure that explained 79,36% of the variance. The two factors identified were 1) people's demotivation in continuing to follow the recommended protective behaviors (neglect) and 2) people's boredom regarding the pandemic-related information (boredom). The pattern of relations between the Pandemic Fatigue Scale and other variables-find through correlation, mediation, and path analyses-and the gender differences-find in the ANOVA analyses-provided strong evidence of the construct validity. Moreover, the PFS was shown to be invariant regarding gender in a multigroup factor confirmatory analysis.Conclusion: The instrument can be of utility for professionals and researchers to assess pandemic fatigue, a variable that can affect the adoption of protective measure to avoid catching and spreading the virus.